PENEGAKAN HUKUM PIDANA DI INDONESIA TERHADAP PENGARUH NEGATIF PERKEMBANGAN CYBER CRIME - Kifli, Susiana (The Juris, 2025)
The rapid development of information and communication technology is also accompanied by the widespread misuse of information and communication technology, so that it becomes a very disturbing problem, namely the occurrence of crimes committed in cyberspace or what is commonly known as "cybercrime". Various crimes have occurred in cyberspace, these cases are certainly detrimental and have negative impacts. Apart from the digital divide, cybercrime in Indonesia is still rampant. The type of research used in this writing is normative legal research. In the discussion of the development of criminal law in the future, in addition to using the law enforcement theory of Soerjono Soekanto, the resolution and prevention of cybercrime must be balanced with the regulation and development of the entire criminal law system, which includes the development of the structure, culture, and substance of criminal law. In such conditions, criminal law policy occupies a strategic position in the development of modern criminal law. Criminal law policy intends to achieve peace and prosperity for all people.